Resistance narratives in patients' accounts of a mandatory pre-operative health optimisation scheme: A qualitative study - Avery-Phipps, Isobel; Hynes, Catherine; Burton, Christopher (Frontiers in Health Services, 2022)
Background Pre-operative Health Optimisation is the engagement of patients in health behavior change, such as smoking cessation and weight reduction prior to surgery. Programmes which routinely delay surgery while some patients undergo preoperative optimisation are increasingly used within the UK. Advocates of this approach argue that it reduces perioperative risk and encourages longer term change at a teachable moment. However, critics have argued that mandatory preoperative optimisation schemes may perpetuate or exacerbate inequalities. Aim To understand patients' experience of a mandatory preoperative optimisation scheme at the time of referral for elective surgery. Design and setting Qualitative interview study in one area of the UK. Method Participants were recruited through GP practices and participating weight-loss schemes. Data was collected from nine semi-structured face-to-face interviews. Thematic analysis was informed by the concept of narratives of resistance. Results Four forms of resistance were found in relation to the programme. Interviewees questioned the way their GPs presented the scheme, suggesting they were acting for the health system rather than their patients. While interviewees accepted personal responsibility for health behaviors, those resisting the scheme emphasized that the wider system carried responsibilities too. Interviewees found referral to the scheme stigmatizing and offset this by distancing themselves from more deviant health behaviors. Finally, interviewees emphasized the logical contradictions between different health promotion messages. Conclusion Patients described negative experiences of mandatory pre-operative health optimisation. Framing them as resistance narratives helps understand how patients contest the imposition of optimisation and highlights the risk of unintended consequences.